Pelatihan Literasi Hukum Terhadap Perlindungan Kekayaan Intelektual Komunal pada Produk Lokal melalui Skema Indikasi Geografis - Ramadhan, Muhammad Citra (Abdimas Indonesian Journal, 2025)
Communal Intellectual Property (CIP) embodies the collective cultural identity that has been passed down through generations within local communities. Nevertheless, limited legal awareness among entrepreneurs and local producers often hinders the optimal protection and utilization of CIP’s cultural and economic value. This community engagement initiative seeks to improve public understanding of the legal aspects surrounding CIP protection, focusing on the Geographical Indication (GI) framework as a legal tool for safeguarding regional products. The program took place at the Grand Mercure Hotel in Medan, in partnership with the Regional Office of the Ministry of Law and Human Rights of North Sumatra, and was broadcast widely through Radio Move Online to ensure broader public outreach. Employing a participatory approach, the program included legal dissemination sessions, educational workshops, and interactive discussions that brought together MSME actors, academics, and local government representatives. The materials addressed the legal foundation of Geographical Indications as stipulated in Law No. 20 of 2016 concerning Trademarks and Geographical Indications, procedural steps for registration, and the economic and reputational advantages for local communities. The outcomes indicated that participants developed a stronger comprehension of the interconnection between CIP and GI, alongside heightened legal consciousness in protecting local products through formal mechanisms. In conclusion, the program successfully enhanced community legal capacity and promoted broader awareness of Communal Intellectual Property protection across North Sumatra.